FREIGHT RESILIENCY PERFORMANCE MEASURES: BELOIT TO HUDSON CORRIDOR - Toledo-Durán, Edwin Josue (My University, 2010)
No one is exempt from emergencies. People, private companies and public agencies, all face the possibility of a sudden event that disrupt their normal functions. Disasters inflict chaos in all aspects of human endeavors and are the source of most disruptions. Recent disasters had raised the need to be able to handle these events. Resiliency is the capacity of a system to absorb the impacts of a disruption, and the ability to reduce impacts and maintain mobility. A fragile system should be transformed into a resilient one. It should be able to provide service during small interruptions and recover quickly from large disruptions. By examining resiliency measures in transportation systems we can understand vulnerabilities in the networks. Resiliency measures may be used to guide infrastructure investments to protect against disruptions and accelerate recovery after a disaster. This thesis was focused on the development of a methodology to estimate resiliency measures using data from the American Truck Research Institute (ATRI), collected through the Freight Performance Measurement Initiative, a partnership between FHWA and ATRI, along an interstate corridor to illustrate measures for freight transportation resiliency. Two resiliency measures, robustness and rapidity, were estimated using freight resiliency triangles during two weather events that affected the Beloit to Hudson corridor in 2008. The corridor was evaluated for seven corridor portions between the cities of Hudson, Eau Claire, Tomah, Mauston, Portage, Madison, Janesville and Beloit, on each direction and each event. The research presents a set of criteria to qualify the computed resiliency measures. These criteria reflect the corridor?s observed behavior during disruptions. It was developed along with the resiliency triangles, which together are a tool to evaluate resiliency.